Development Of Fitness Test Results Measurement For Karate Sports Based On Application - Maryani, Maryani; Hartati (UNIB Press, 2024)
This research aims to develop a product in the form of a technology-based application to measure physical fitness test results. This research produced an application for measuring physical fitness test results. The study employed the ADDIE development research method, which consists of the stages of analysis, design, development, implementation, and evaluation.The research subjects were 30 students from junior high school 1 Indralaya, consisting of 20 male students and 10 female students. The study was validated by three experts: a karate sports test and measurement expert (94%, categorized as very feasible), a language expert (82%, categorized as very feasible), and an application expert (97%, categorized as very feasible), using questionnaires containing various questions. The average result from these three validations was 91%, indicating that the application for measuring physical fitness test results in the karate sports branch is feasible to use. However, based on the statistical trial results, the normality test was 0.233, the homogeneity test was 0.118, and the independent sample t-test was 0.118. These results led to the conclusion that the application-based measurement of physical fitness test results developed in this study is valid and effective, making it suitable for use in teaching and learning activities.